The Self‐Testing AfRica (STAR) Initiative: accelerating global access and scale‐up of HIV self‐testing. (25th March 2019) - Ingold, Heather; Mwerinde, Ombeni; Ross, Anna Laura; Leach, Ross; Corbett, Elizabeth L; Hatzold, Karin; Johnson, Cheryl C; Ncube, Getrude; Nyirenda, Rose; Baggaley, Rachel C
Abstract: Introduction: HIV self‐testing (HIVST) was first proposed as an additional option to standard HIV testing services in the 1980s. By 2015, two years after the first HIVST kit was approved for the American market and the year in which Unitaid invested in the "HIV Self‐Testing AfRica (STAR) Initiative, " HIVST remained unexplored with negligible access in low‐ and middle‐income countries (LMIC). However, rapid progress had been made. This commentary outlines the interlinked market, regulatory and policy barriers that had inhibited product development and kept HIVST out of LMIC policy. We detail the components of STAR that enabled rapid HIVST scale‐up, including critical investments in implementation, research, market forecasting, and engagement with manufacturers and regulators. Discussion: The STAR Initiative has generated crucial information about how to distribute HIVST products effectively, ethically and efficiently. Service delivery models range from clinic‐based distribution to workplace and partner‐delivered approaches to reach first‐time male testers, to community outreach to sex workers and general population "hotspots." These data directly informed supportive policy, notably the 2016 WHO guidelines strongly recommending HIVST as an additional testing approach, and regulatory change through support for WHO prequalification of the first HIVST kit in 2017. In July 2015, only two countries had national HIVST policies and were implementing HIVST. Three years later, 59 countries have policies, actively implemented in 28, with an additional 53 countries reporting policies under development. By end‐November 2018 several quality‐assured HIVST products had been registered, including two WHO prequalified tests. STAR Initiative countries have drafted regulations governing in vitro diagnostics, including HIVST products. With enabling policies, pre‐qualification and regulations in place, donor procurement of kits has increased rapidly, to a forecasted estimate of 16 million HIVST kits procured by 2020. Conclusions: The STAR Initiative provided a strong foundation to introduce HIVST in LMICs and allow for rapid scale‐up based on the wealth of multi‐country evidence gathered. Together with sustained coordination and acceleration of market development work, HIVST can help address the testing gap and provide a focused and cost‐effective means to expand access to treatment and prevention services.